Characterization of actinomycetes antagonistic to Phytophthora fragariae var. rubi, the causal agent of raspberry root rot - Toussaint, V.; Valois, D.; Dodier, M.; Faucher, E.; Déry, C.; Brzezinski, R.; Ruest, L.; Beaulieu, C. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
Eleven actinomycete strains that were previously shown to protect raspberry (Rubus strigosus) plants against Phytophthora infection were characterized. all were shown to belong to the genus Streptomyces. Two strains (EF-34 and EF-76) grew at 4, 15 and 30°C on V8 agar between pHs 5 to 9. Seven strains including EF-34 and EF-76 had both the ability to hydrolyze Phytophthora cell walls and to inhibit Phytophthora growth at 15°C between pHs 5 to 9. all actinomycetes inhibited the growth of P. fragariaevar. rubi and of Pythium ultimum. The growth of other fungal species and of Gram-negative bacteria was inhibited only in the presence of three strains (EF-14, EF-72, and EF-76). The eleven antagonistic actinomycetes were classified into four groups with regard to their resistance to various pesticides used to protect raspberry crops. Strain EF-76 was further characterized. This strain was identified as Streptomyceshygroscopicus var. geldanus, and it was shown to produce geldanamycin, a known antibiotic.